Papers - Properties of Metals - Effect of Alloying on the Permissible Fiber Stress ill Corrugated Zinc Roofing (With Discussion) - E. A. Anderson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1930)
In another paper' the writer has shown that the low permissible maximum fiber stress in a loaded zinc sheet demands a much closer support spacing than is used for steel. The limiting fiber stress in 13-gage (0.032 in.) sheets having a 1-in. depth of corrugation was found to be about 5000 lb. per sq. in. on a 37-in. span under a load of 40 Ib. per sq. ft. Corrugated steel sheets are commonly laid with spans varying from 48 to 60 in. In order to increase the span in 13-gage zinc to 54 in. (a common spacing) the metal must be capable of withstanding, under long-continued loading, a maximum fiber stress of about 10,000 lb. per sq. in. This is known to be impossible with unalloyed zinc. In this paper the writer describes a series of experiments leading up to the development of an alloy capable of safely sustaining this fiber stress. The effect of alloying on the slow creep of zinc was studied by means of static tensile tests, accurate determinations of apparent elastic limits and finally by means of loading tests on full-size roof sections. Two industrial buildings roofed with alloyed zinc sheets on spans involving fiber stresses in excess of 10,000 lb. per sq. in. have been under observation for over two years without signs of sagging. Experimental Work Two methods of increasing the maximum permissible fiber stress in zinc were considered. Cold rolling, which' increases the stiffness and tensile strength, was found to decrease the resistance to slow flow. Alloying, therefore, provided the only feasible means of obtaining the desired result, It was recognized that the improvement secured by the solid solution of natural impurities was insufficient. A series of alloys was outlined, therefore, in which a number of metals were added separately and together. The sheets rolled from these alloys were tested under